SFB754 SADCP data (velocities and backscatter) - Gerd Krahmann; Hela Mehrtens (PANGAEA, 2021)
SADCP data were acquired on 33 of the research cruises On FS Meteor, FS Maria S. Merian and FS Sonne II two Teledyne RDI Ocean Surveyor systems with 38 and 75 kHz transmission frequency were used, while on NO l extquotesingleAtalante a single 75 kHz system was used. All data was processed with a software package developed at GEOMAR following the GO-SHIP standards (Firing and Hummon, 2010). The data was subsequently averaged over one minute intervals, converted to a NetCDF based format and published. For a small number of cruises, the signal strength information of the SADCP data has also been used to estimate the backscatter in the ocean. These data sets were processed following Mullinson (2017) and published separately from the regular SADCP data (see also Table C7).